0246 Weekend work and Psychosocial Well-being in Korean workers. (23rd June 2014) - Lee, Hye-Eun; Kim, Hyoung-Ryoul; Kim, In-Ah
Abstract : Objectives: To identify association between weekend work and psychosocial well-being in a representative sample of Korean workers. Method: We analysed the associations between weekend work and psychosocial well-being in 29 711 workers using data from the 2011 Korean Working Conditions Survey. Weekend work was defined by working one or more day on Saturday or on Sunday over the last month. Psychosocial well-being was measured by WHO well-being index. Multiple logistic regression analysis was performed adjusting age, education, income, regular/non-regular work, working time with stratifying sex and shift-work. Results: The prevalence of weekend work was higher in male (62.4%) than in female (54.8%). The longer working time per week, the more employees worked weekend [<40 (42.6%), 40–48 (45.3%), 49–60 (80.6%), ≥61 (94.9%)]. Shift workers (87.3%) worked more than non-shift workers (56.2%) on weekend. In non-shift workers, weekend work group (≤4 days) [OR=1.34 (95% CI 1.22–1.48), OR=1.17 (95% CI 1.05–1.31)]and weekend work group (>4 days) [OR=1.19 (95% CI 1.03–1.38), OR=1.30 (95% CI 1.10–1.52)] were significant risk factors associated with lesser psychosocial well-being in male and female respectively. Conclusions: Weekend work is associated with a significant increase in lesser psychosocial well-being among Korean non-shift workers.